Reflections on the future of research, development and innovation in Colombia - De Martinis, Domenico; Bon, Paola (ObIES, 2017)
Colombia is going through a moment of historical change. After four years of formal peace negotiations and the signing of a peace agreement with the FARC in November 2016, the country is set to enter an era of increased stability. In this perspective, the Colombian government should concentrate its effort to respond to societal challenges by improving infrastructure, promoting social inclusion and a sustainable use of natural resources. However, while it is acknowledged that greater investments in science and technology could foster economic growth and development and respond to societal needs, Colombia is still lagging behind. Greater investment in science and technology with a long-term perspective should support the country’s efforts for growth and development. Furthermore, considering Colombia´s great diversity in terms of population, topography and societal needs, it appears reductive to apply a ‘one size fits all’ solution. This article presents some reflections on how strengthening the capacity of higher education institutions (HEIs) for research and internationalization and strengthening the link between knowledge, practice and policy would contribute to more and better research, development and innovation in Colombia.